The Value of Peripheral Enhancement Pattern for Diagnosing Thyroid Cancer Using Contrast-Enhanced Ultrasound - Yan Zhang; Ming-bo Zhang; Yu-kun Luo; Jie Li; Zhi-li Wang; Jie Tang (International Journal of Endocrinology)
Background. Contrast-enhanced ultrasound (CEUS) scanning can detect differences between thyroid tumors and surrounding tissues. However, enhancement patterns within nodules are insufficient for the diagnosis of thyroid carcinomas. The peripheral enhancement patterns of nodules may provide useful diagnostic information. The objective of this study was to investigate the diagnostic accuracy of the peripheral enhancement patterns during CEUS scanning of thyroid nodules. Material and Methods. 120 nodules with peripheral rings during CEUS and definite pathology confirmed by surgery were included in this study. The internal and peripheral CEUS enhancement patterns of these nodules were assessed, and the diagnostic value of CEUS was compared with the conventional ultrasound. The relationship of types of peripheral rings and sizes of nodules was analyzed, respectively. Results. There were 78 benign and 42 malignant nodules. Peripheral irregular ring performs well in detecting malignancy. It improves the diagnostic performance of CEUS by combining with internal enhancement patterns (diagnostic sensitivity of 97.6%, specificity of 98.7%, and accuracy of 98.3%) and adds value to conventional ultrasound (95.2%, 70.5%, and 79.2%). The sizes of the nodules with regular high-enhanced rings (2.34 ± 1.33 cm) were larger than the other three types of peripheral rings (P<0.05). Conclusions. Features of peripheral ring on CEUS are important for the diagnosis of thyroid cancer; they can further contribute to the accuracy combining with the internal enhancement pattern, which could avoid the unnecessary biopsy.